Concrete composite tackifier and preparation method thereof

Through the combination of modified polyacrylic acid resin and modified silicon ash, a composite concrete composite adhesive with good compatibility and antibacterial properties is prepared, which solves the poor compatibility of adhesive compatibility and lack of antibacterial functions in existing technologies. The problem significantly improves the performance and service life of concrete.

CN119371136AActive Publication Date: 2025-01-28GANSU JINKAINING IND & TRADE GRP CO LTD

Patent Information

Application Number
CN202411907060.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing concrete tackifiers have poor compatibility with polycarboxylic acid-based water reducing agents and lack antibacterial functions, making it difficult to effectively prevent the growth and diffusion of microorganisms on the surface or inside of the concrete.

Method used

The modified polyacrylic resin and the modified silicon ash are combined with a composite adhesive of the concrete. The modified polyacrylate resin has antibacterial performance through sulfonation and seasonal salt. Essence

Benefits of technology

Realize the good compatibility of the water reducing agent with polycarboxylic acid, enhance the water retention and adhesion of the concrete, and have effective inhibitory or kill the antibacterial properties of microorganisms, extend the service life of concrete and ensure the building of the building Hygiene and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a concrete composite tackifier and a preparation method thereof, and relates to the technical field of concrete. When the concrete composite tackifier is prepared, firstly, polyacrylic resin obtained by polymerizing acrylic acid, methyl methacrylate, acrylamide and vinyl diphenylphosphine reacts with modified porphyrin, and then sulfonation is performed to obtain modified polyacrylic resin; the preparation method comprises the following steps: firstly, pre-treating silica fume with vinyltrimethoxysilane, then carrying out a reaction on the silica fume pre-treated with vinyltrimethoxysilane, tetravinyltetramethylcyclotetrasiloxane and vinylboronic acid pinacol ester to obtain modified silica fume, and finally, mixing polyacrylic resin and the modified silica fume to obtain the concrete composite tackifier. The concrete composite tackifier prepared by the invention has good working performance and antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to a concrete composite viscosity enhancer and a preparation method thereof. Background Art

[0002] Concrete viscosity enhancer, as a professional chemical additive, is designed to optimize and enhance the overall performance of concrete. It is a special compound that can significantly improve the fluidity, ductility and adhesion of concrete, making it easier to handle and control during construction.

[0003] Concrete thickeners are usually composed of high molecular polymers, inorganic sols or other special compounds, which can interact with cement particles, aggregates and water in concrete in a complex manner. When thickeners are added to concrete, their high molecular chains quickly penetrate into the concrete and form a close adsorption and wrapping relationship with cement particles. This adsorption not only increases the bonding force between cement particles, but also makes the overall structure of concrete more compact and stable.

[0004] However, there are some shortcomings in the concrete thickeners currently on the market, especially the poor compatibility of most of the concrete thickeners on sale with polycarboxylic acid water reducers; in addition, these thickeners often lack antibacterial function, and it is difficult to effectively prevent bacteria, fungi and other microorganisms from growing and spreading on the surface or inside of concrete. The growth and spread of microorganisms will not only shorten the service life of concrete, but also may pose a threat to the health and safety of buildings, affecting people's living comfort. Therefore, it is urgent to develop a new type of concrete thickener, which not only has excellent thickening performance, but also has good compatibility with polycarboxylic acid water reducers, and can effectively inhibit or kill microorganisms, so as to ensure the service life of concrete and the health and safety of buildings, and create a healthier and more comfortable living environment for people. Summary of the invention

[0005] The purpose of the present invention is to provide a concrete composite viscosity increasing agent and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention discloses a composite concrete viscosity enhancer, which is prepared by mixing modified polyacrylic acid resin and modified silica fume.

[0007] As an optimization, the modified polyacrylic acid resin is prepared by reacting a polyacrylic acid resin obtained by polymerization of acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine with modified porphyrin, followed by sulfonation.

[0008] As an optimization, the modified silica fume is obtained by reacting silica fume pretreated with vinyltrimethoxysilane with tetravinyltetramethylcyclotetrasiloxane and vinylboric acid pinacol ester.

[0009] A method for preparing a concrete composite viscosity enhancer comprises the following preparation steps: (1) Acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine are mixed in a mass ratio of 15:15:20:5 to obtain a monomer mixture; the monomer mixture, azobisisobutyronitrile and isopropanol are weighed in a mass ratio of 50:1:49, 20%-30% of the monomer mixture, 20%-30% of azobisisobutyronitrile and 60%-70% of isopropanol are mixed to obtain a solution A, and the remaining monomer mixture, azobisisobutyronitrile and isopropanol are mixed to obtain a solution B, the solution A is heated to 85°C and refluxed with stirring for 30-40 minutes, and then the solution B is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the solution is stirred at 85°C for 4-5 hours, the temperature is lowered to 50-60°C, triethylamine is added to adjust the pH to 6-7, the reaction is continued for 0.5 hours, and the polyacrylic acid resin is obtained by rotary evaporation under reduced pressure and vacuum drying; (2) p-Chlorobenzaldehyde, benzaldehyde, pyrrole, iodine, and p-chlorobenzoquinone are weighed in a molar ratio of 1:3:4:0.4:3; p-Chlorobenzaldehyde, benzaldehyde, iodine, and pyrrole are sequentially added to dichloromethane with a mass 20 times that of p-chlorobenzaldehyde, and after a first activation, p-chlorobenzoquinone is added and a second activation is performed to obtain a mixture, the mixture is evaporated on fluorosilica, and purified by flash chromatography to obtain a modified porphyrin; (3) Mix polyacrylic acid resin, modified porphyrin and isopropanol in a mass ratio of 1:(0.2-0.3):(20-30), heat to 100°C and reflux for reaction for 10-12h, and vacuum dry by rotary evaporation to obtain functionalized polyacrylic acid resin; prepare a 0.2g / mL solution of functionalized polyacrylic acid resin and N,N-dimethylformamide, add 99wt% concentrated hydrochloric acid (12 times the mass of functionalized polyacrylic acid resin) to the solution at a dropping speed of 1mL / min, heat to 40°C and react for 2h, and after the reaction is completed, vacuum evaporation and vacuum drying are performed to obtain modified polyacrylic acid resin; (4) Pretreated silica ash, tetravinyltetramethylcyclotetrasiloxane, vinylboronic acid pinacol ester, azobisisobutyronitrile, and N,N-dimethylformamide were mixed in a mass ratio of 1:(0.3-0.4):(0.1-0.2):(50-60), ultrasonically mixed, heated to 70-80°C for reaction for 2-3h, and after the reaction was completed, filtered and washed with pure water for 3-4 times to obtain modified silica ash; (5) Mix the modified polyacrylic acid resin and modified silica fume in a mass ratio of 1:(0.05-0.1) to obtain a concrete composite viscosity enhancer.

[0010] As an optimization, the eluent of the flash chromatography in step (2) is ethyl acetate / chloroform, and the elution gradient of the eluent is ethyl acetate:chloroform volume ratio from 8:2 to 1:9.

[0011] As an optimization, the first activation in step (2) is microwave activation with a microwave power of 100 W, a temperature of 30° C., and a time of 30 min; the second activation is microwave activation with a microwave power of 100 W, a temperature of 30° C., and a time of 1 min.

[0012] As an optimization, the preparation method of the pretreated silica ash in step (4) is as follows: vinyltrimethoxysilane, anhydrous ethanol and pure water are mixed at a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of vinyltrimethoxysilane is added to silica ash, the temperature is raised to 110°C, reflux reaction is carried out for 3-4 hours, filtering and washing with anhydrous ethanol for 4 times, and vacuum drying to obtain the pretreated silica ash.

[0013] As an optimization, the specific surface area of ​​the silica ash is 25m 2 / g.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the composite concrete tackifier, the present invention comprises the following steps: firstly, a polyacrylic acid resin obtained by polymerizing acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine is reacted with modified porphyrin, and then sulfonated to obtain the modified polyacrylic acid resin; secondly, silica fume pretreated with vinyl trimethoxy silane is reacted with tetravinyl tetramethyl cyclotetrasiloxane and vinyl boric acid pinacol ester to obtain the modified silica fume; and finally, the polyacrylic acid resin and the modified silica fume are mixed to obtain the composite concrete tackifier.

[0015] First, acrylic acid, methyl methacrylate, acrylamide, and vinyl diphenyl phosphine are polymerized to form a polyacrylic acid resin with a polymer chain, and a diphenyl phosphine structure is grafted on the side chain, which is then reacted with the chlorophenyl group on the modified porphyrin to form a quaternary phosphonium salt. The quaternary phosphonium salt has good antibacterial properties, and then sulfonated with concentrated hydrochloric acid to graft hydrophilic sulfonic acid groups on the polyacrylic acid resin to increase water retention. The polyacrylic acid molecular chain contains not only negatively charged carboxyl groups and negatively charged sulfonic acid groups, but also positively charged quaternary phosphonium cations. The presence of these charges enables the polymer chains to interact with each other through electrostatic attraction, thereby achieving cross-linking and enhancing its viscosity. The presence of the porphyrin structure can well complex the calcium ions in the cement and enhance the viscosity. Secondly, the silica fume pretreated with vinyl trimethoxysilane contains double bonds. Under the action of the initiator, tetravinyl tetramethyl cyclotetrasiloxane and vinyl boric acid pinacol ester can polymerize on the surface of silica fume, thereby grafting cyclosiloxane and boric acid pinacol ester structures on the surface of silica fume. As an expansive inorganic material with a high specific surface area, silica fume can increase the water retention of concrete. During the cement hydration process, the alkalinity in the environment gradually increases. Under alkaline conditions, the cyclosiloxane structure and boric acid pinacol ester structure grafted on the surface of silica fume will gradually hydrolyze. Cyclosiloxane hydrolyzes and ring-opens to form a silanol structure, and boric acid pinacol ester hydrolyzes to form a boric acid structure. The silanol structure and boric acid structure have a good adsorption effect on cement and can penetrate into the interior of the concrete, forming a close adsorption and wrapping relationship with cement particles, which not only increases the bonding force between cement particles, but also makes the overall structure of concrete more compact and stable. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0017] The specific surface area of ​​the silica fume used in the following examples and comparative examples is 25 m 2 / g.

[0018] Embodiment 1: A method for preparing a composite concrete tackifier, the method comprising the following steps: (1) Acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine are mixed in a mass ratio of 15:15:20:5 to obtain a monomer mixture; the monomer mixture, azobisisobutyronitrile and isopropanol are weighed in a mass ratio of 50:1:49, 20% of the monomer mixture, 20% of azobisisobutyronitrile and 60% of isopropanol are mixed to obtain a solution A, and the remaining monomer mixture, azobisisobutyronitrile and isopropanol are mixed to obtain a solution B, the solution A is heated to 85°C and refluxed with stirring for 40 minutes, and then the solution B is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the solution is stirred at 85°C for 5 hours, the temperature is lowered to 60°C, triethylamine is added to adjust the pH to 7, the reaction is continued for 0.5 hours, and the polyacrylic acid resin is obtained by rotary evaporation under reduced pressure and vacuum drying; (2) p-Chlorobenzaldehyde, benzaldehyde, pyrrole, iodine and p-chlorobenzoquinone were weighed in a molar ratio of 1:3:4:0.4:3; p-Chlorobenzaldehyde, benzaldehyde, iodine and pyrrole were added to dichloromethane (20 times the mass of p-chlorobenzaldehyde) in sequence, and activated for the first time, wherein the first activation was microwave activation with a microwave power of 100 W, a temperature of 30°C and a time of 30 min; p-Chlorobenzaldehyde was added and activated for the second time, wherein the second activation was microwave activation with a microwave power of 100 W, a temperature of 30°C and a time of 1 min to obtain a mixture, the mixture was evaporated on fluorosilicic acid, and purified by flash chromatography to obtain a modified porphyrin; the eluent for the flash chromatography was ethyl acetate / chloroform, and the elution gradient of the eluent was ethyl acetate:chloroform volume ratio from 8:2 to 1:9; (3) Mix polyacrylic acid resin, modified porphyrin and isopropanol in a mass ratio of 1:0.2:20, heat to 100°C and reflux for reaction for 12 hours, and vacuum dry by rotary evaporation to obtain functionalized polyacrylic acid resin; prepare a 0.2 g / mL solution of functionalized polyacrylic acid resin and N,N-dimethylformamide, add 99 wt% concentrated hydrochloric acid (12 times the mass of functionalized polyacrylic acid resin) to the solution at a dropping speed of 1 mL / min, heat to 40°C and react for 2 hours, and after the reaction is completed, vacuum evaporation and vacuum drying are performed to obtain modified polyacrylic acid resin; (4) Vinyltrimethoxysilane, anhydrous ethanol and pure water were mixed at a mass ratio of 1:1:5 for 10 minutes, and silica ash with a mass of 0.5 times that of vinyltrimethoxysilane was added, and the temperature was raised to 110°C, and refluxed for 3 hours. The mixture was filtered and washed with anhydrous ethanol for 4 times, and vacuum dried to obtain pretreated silica ash. The pretreated silica ash, tetravinyltetramethylcyclotetrasiloxane, vinylboronic acid pinacol ester, azobisisobutyronitrile and N,N-dimethylformamide were mixed at a mass ratio of 1:0.3:0.1:50, and ultrasonically mixed. The mixture was heated to 80°C for 3 hours. After the reaction was completed, the mixture was filtered and washed with pure water for 4 times to obtain modified silica ash. (5) The modified polyacrylic acid resin and the modified silica fume are mixed in a mass ratio of 1:0.05 to obtain a concrete composite viscosity enhancer.

[0019] Embodiment 2: A method for preparing a composite concrete tackifier, the method comprising the following steps: (1) Acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine are mixed in a mass ratio of 15:15:20:5 to obtain a monomer mixture; the monomer mixture, azobisisobutyronitrile and isopropanol are weighed in a mass ratio of 50:1:49, 25% of the monomer mixture, 25% of azobisisobutyronitrile and 65% of isopropanol are mixed to obtain a solution A, and the remaining monomer mixture, azobisisobutyronitrile and isopropanol are mixed to obtain a solution B, the solution A is heated to 85°C and refluxed with stirring for 35 minutes, and then the solution B is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the solution is stirred at 85°C for 4.5 hours, the temperature is lowered to 55°C, triethylamine is added to adjust the pH to 6.5, the reaction is continued for 0.5 hours, and the polyacrylic acid resin is obtained by rotary evaporation under reduced pressure and vacuum drying; (2) p-Chlorobenzaldehyde, benzaldehyde, pyrrole, iodine and p-chlorobenzoquinone were weighed in a molar ratio of 1:3:4:0.4:3; p-Chlorobenzaldehyde, benzaldehyde, iodine and pyrrole were added to dichloromethane (20 times the mass of p-chlorobenzaldehyde) in sequence, and activated for the first time, wherein the first activation was microwave activation with a microwave power of 100 W, a temperature of 30°C and a time of 30 min; p-Chlorobenzaldehyde was added and activated for the second time, wherein the second activation was microwave activation with a microwave power of 100 W, a temperature of 30°C and a time of 1 min to obtain a mixture, the mixture was evaporated on fluorosilicic acid, and purified by flash chromatography to obtain a modified porphyrin; the eluent for the flash chromatography was ethyl acetate / chloroform, and the elution gradient of the eluent was ethyl acetate:chloroform volume ratio from 8:2 to 1:9; (3) Mix polyacrylic acid resin, modified porphyrin and isopropanol in a mass ratio of 1:0.25:25, heat to 100°C and reflux for reaction for 11 hours, and vacuum dry by rotary evaporation to obtain functionalized polyacrylic acid resin; prepare a 0.2 g / mL solution of functionalized polyacrylic acid resin and N,N-dimethylformamide, add 99 wt% concentrated hydrochloric acid (12 times the mass of functionalized polyacrylic acid resin) to the solution at a dropping speed of 1 mL / min, heat to 40°C and react for 2 hours, and after the reaction is completed, vacuum evaporation and vacuum drying are performed to obtain modified polyacrylic acid resin; (4) Vinyltrimethoxysilane, anhydrous ethanol and pure water were mixed at a mass ratio of 1:1:5 for 10 minutes, and silica ash with a mass of 0.5 times that of vinyltrimethoxysilane was added, and the temperature was raised to 110°C, and the reaction was refluxed for 3.5 hours. The silica ash was filtered and washed with anhydrous ethanol for 4 times, and vacuum dried to obtain pretreated silica ash; the pretreated silica ash, tetravinyltetramethylcyclotetrasiloxane, vinylboronic acid pinacol ester, azobisisobutyronitrile and N,N-dimethylformamide were mixed at a mass ratio of 1:0.35:0.15:55, and ultrasonically mixed. The temperature was raised to 75°C for reaction for 2.5 hours. After the reaction was completed, the silica ash was filtered and washed with pure water for 3 times to obtain modified silica ash; (5) The modified polyacrylic acid resin and the modified silica fume are mixed in a mass ratio of 1:0.07 to obtain a concrete composite viscosity enhancer.

[0020] Embodiment 3: A method for preparing a composite concrete tackifier, the method comprising the following steps: (1) Acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine are mixed in a mass ratio of 15:15:20:5 to obtain a monomer mixture; the monomer mixture, azobisisobutyronitrile and isopropanol are weighed in a mass ratio of 50:1:49, 30% of the monomer mixture, 30% of azobisisobutyronitrile and 70% of isopropanol are mixed to obtain a solution A, and the remaining monomer mixture, azobisisobutyronitrile and isopropanol are mixed to obtain a solution B, the solution A is heated to 85°C and refluxed with stirring for 30 minutes, and then the solution B is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the solution is stirred at 85°C for 4 hours, the temperature is lowered to 50°C, triethylamine is added to adjust the pH to 6, the reaction is continued for 0.5 hours, and the polyacrylic acid resin is obtained by rotary evaporation under reduced pressure and vacuum drying; (2) p-Chlorobenzaldehyde, benzaldehyde, pyrrole, iodine and p-chlorobenzoquinone were weighed in a molar ratio of 1:3:4:0.4:3; p-Chlorobenzaldehyde, benzaldehyde, iodine and pyrrole were added to dichloromethane (20 times the mass of p-chlorobenzaldehyde) in sequence, and activated for the first time, wherein the first activation was microwave activation with a microwave power of 100 W, a temperature of 30°C and a time of 30 min; p-Chlorobenzaldehyde was added and activated for the second time, wherein the second activation was microwave activation with a microwave power of 100 W, a temperature of 30°C and a time of 1 min to obtain a mixture, the mixture was evaporated on fluorosilicic acid, and purified by flash chromatography to obtain a modified porphyrin; the eluent for the flash chromatography was ethyl acetate / chloroform, and the elution gradient of the eluent was ethyl acetate:chloroform volume ratio from 8:2 to 1:9; (3) Mix polyacrylic acid resin, modified porphyrin and isopropanol in a mass ratio of 1:0.3:30, heat to 100°C and reflux for reaction for 10 hours, and vacuum dry by rotary evaporation to obtain functionalized polyacrylic acid resin; prepare a 0.2 g / mL solution of functionalized polyacrylic acid resin and N,N-dimethylformamide, add 99 wt% concentrated hydrochloric acid (12 times the mass of functionalized polyacrylic acid resin) to the solution at a dropping speed of 1 mL / min, heat to 40°C and react for 2 hours, and after the reaction is completed, vacuum evaporation and vacuum drying are performed to obtain modified polyacrylic acid resin; (4) Vinyltrimethoxysilane, anhydrous ethanol and pure water were mixed at a mass ratio of 1:1:5 for 10 minutes, and silica ash with a mass of 0.5 times that of vinyltrimethoxysilane was added, the temperature was raised to 110°C, refluxed for 3 hours, filtered and washed with anhydrous ethanol for 4 times, and vacuum dried to obtain pretreated silica ash; the pretreated silica ash, tetravinyltetramethylcyclotetrasiloxane, vinylboronic acid pinacol ester, azobisisobutyronitrile and N,N-dimethylformamide were mixed at a mass ratio of 1:0.4:0.2:60, ultrasonically mixed, heated to 70°C for 2 hours, and filtered and washed with pure water for 3 times to obtain modified silica ash; (5) The modified polyacrylic acid resin and the modified silica fume are mixed in a mass ratio of 1:0.1 to obtain a concrete composite viscosity enhancer.

[0021] Comparative Example 1: The preparation method of the composite concrete tackifier of Comparative Example 1 differs from that of Example 2 in that the method does not contain steps (2) to (3), and step (1) is modified as follows: acrylic acid, methyl methacrylate, acrylamide, and vinyl diphenyl phosphine are mixed in a mass ratio of 15:15:20:5 to obtain a monomer mixture; the monomer mixture, azobisisobutyronitrile, and isopropanol are weighed in a mass ratio of 50:1:49, 25% of the monomer mixture, 25% of azobisisobutyronitrile, and 65% of isopropanol are mixed to obtain a solution A; the remaining monomer mixture, azobisisobutyronitrile, and isopropanol are mixed to obtain a solution B; the solution A is heated to 85° C. and refluxed and stirred for 35 min, and then the solution B is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the solution is stirred at 85° C. for 4.5 h, cooled to 55° C., triethylamine is added to adjust the pH to 6.5, the reaction is continued for 0.5 h, and the modified polyacrylic acid resin is obtained by rotary evaporation under reduced pressure and vacuum drying.

[0022] Comparative Example 2: The preparation method of the composite concrete tackifier of Comparative Example 2 differs from that of Example 2 in that step (4) is not included, and step (5) is modified as follows: the modified polyacrylic acid resin and silica fume are mixed in a mass ratio of 1:0.07 to obtain the composite concrete tackifier.

[0023] Test Example 1: The concrete composite viscosity enhancers of Examples 1 to 3 and Comparative Examples 1 to 2 were applied to concrete, the mix ratio of the concrete was shown in Table 1, and the performance test of the concrete was carried out. The results are shown in Table 2.

[0024] Table 1 Concrete mix ratio (kg / m 3 )

[0025] Among them, the cement is PO 42.5 grade cement; the fly ash is F class I fly ash; the mineral powder is S95 grade mineral powder; the machine-made sand is limestone zone II machine-made sand, the fine stone particle size is 5-10mm, the coarse stone particle size is 10-20mm, and the water reducer is Ujion-PC polycarboxylate water reducer produced by Wuhan Yuanjin Building Materials Co., Ltd.

[0026] The concrete performance was tested with reference to GB / T 8076-2008 "Concrete Admixtures" and GB / T50080-2002 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures". The blank group was concrete without adding viscosity enhancer. The test results are shown in Table 2.

[0027] Table 2

[0028] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 2, it can be found that the concrete composite viscosity enhancer prepared by the present invention has good working performance.

[0029] By comparison, the slump of the tackifier of Examples 1 to 3 is greater than that of Comparative Examples 1 to 2, and the expansion is less than that of Comparative Examples 1 to 2, indicating that first, acrylic acid, methyl methacrylate, acrylamide, and vinyl diphenyl phosphine are polymerized to form a polyacrylic acid resin having a polymer chain, and a diphenyl phosphine structure is grafted on the side chain, and then reacted with the chlorophenyl group on the modified porphyrin to form a quaternary phosphonium salt, which has good antibacterial properties, and then sulfonated with concentrated hydrochloric acid to graft a hydrophilic sulfonic acid group on the polyacrylic acid resin to increase water retention; the polyacrylic acid molecular chain contains not only negatively charged carboxyl groups and negatively charged sulfonic acid groups, but also positively charged quaternary phosphonium cations, and the presence of these charges enables the polymer chains to interact with each other through electrostatic attraction, thereby achieving crosslinking, and thus enhancing its viscosity; the presence of the porphyrin structure can well complex calcium ions in cement to enhance viscosity; Secondly, the silica fume pretreated with vinyl trimethoxysilane contains double bonds. Under the action of the initiator, tetravinyl tetramethyl cyclotetrasiloxane and vinyl boric acid pinacol ester can polymerize on the surface of silica fume, thereby grafting cyclosiloxane and boric acid pinacol ester structures on the surface of silica fume. As an expansive inorganic material with a high specific surface area, silica fume can increase the water retention of concrete. During the cement hydration process, the alkalinity in the environment gradually increases. Under alkaline conditions, the cyclosiloxane structure and boric acid pinacol ester structure grafted on the surface of silica fume will gradually hydrolyze. Cyclosiloxane hydrolyzes and ring-opens to form a silanol structure, and boric acid pinacol ester hydrolyzes to form a boric acid structure. The silanol structure and boric acid structure have a good adsorption effect on cement and can penetrate into the interior of the concrete, forming a close adsorption and wrapping relationship with cement particles, which not only increases the bonding force between cement particles, but also makes the overall structure of concrete more compact and stable.

[0030] Test Example 2: Antibacterial performance test: Test method: Referring to the standard GB / T 21510-2008, the antibacterial properties of the concrete composite viscosity enhancers prepared in the examples and comparative examples were tested by the oscillation method. The results are shown in Table 3.

[0031] Table 3

[0032] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 3, it can be found that the concrete composite viscosity enhancer prepared by the present invention has good antibacterial properties.

[0033] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that acrylic acid, methyl methacrylate, acrylamide, and vinyl diphenyl phosphine are polymerized to form a polyacrylic resin with a polymer chain, and a diphenyl phosphine structure is grafted on the side chain, which then reacts with the chlorophenyl group on the modified porphyrin to form a quaternary phosphonium salt, and the quaternary phosphonium salt has good antibacterial properties.

[0034] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A concrete composite viscosity enhancer, characterized in that: The concrete composite viscosity enhancer is prepared by mixing modified polyacrylic acid resin and modified silica fume; The modified polyacrylic acid resin is prepared by reacting a polyacrylic acid resin obtained by polymerization of acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine with modified porphyrin, followed by sulfonation. The modified silica fume is obtained by reacting silica fume pretreated with vinyltrimethoxysilane with tetravinyltetramethylcyclotetrasiloxane and vinylboric acid pinacol ester.

2. A method for preparing a composite concrete viscosity enhancer, characterized in that: The method comprises the following preparation steps: (1) Acrylic acid, methyl methacrylate, acrylamide and vinyl diphenyl phosphine are mixed in a mass ratio of 15:15:20:5 to obtain a monomer mixture; the monomer mixture, azobisisobutyronitrile and isopropanol are weighed in a mass ratio of 50:1:49, 20%-30% of the monomer mixture, 20%-30% of azobisisobutyronitrile and 60%-70% of isopropanol are mixed to obtain a solution A, and the remaining monomer mixture, azobisisobutyronitrile and isopropanol are mixed to obtain a solution B, the solution A is heated to 85°C and refluxed with stirring for 30-40 minutes, and then the solution B is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the solution is stirred at 85°C for 4-5 hours, the temperature is lowered to 50-60°C, triethylamine is added to adjust the pH to 6-7, the reaction is continued for 0.5 hours, and the polyacrylic acid resin is obtained by rotary evaporation under reduced pressure and vacuum drying; (2) p-Chlorobenzaldehyde, benzaldehyde, pyrrole, iodine, and p-chlorobenzoquinone are weighed in a molar ratio of 1:3:4:0.4:3; p-Chlorobenzaldehyde, benzaldehyde, iodine, and pyrrole are sequentially added to dichloromethane with a mass 20 times that of p-chlorobenzaldehyde, and after a first activation, p-chlorobenzoquinone is added and a second activation is performed to obtain a mixture, the mixture is evaporated on fluorosilica, and purified by flash chromatography to obtain a modified porphyrin; (3) Mix polyacrylic acid resin, modified porphyrin and isopropanol in a mass ratio of 1:(0.2-0.3):(20-30), heat to 100°C and reflux for reaction for 10-12h, and vacuum dry by rotary evaporation to obtain functionalized polyacrylic acid resin; prepare a 0.2g / mL solution of functionalized polyacrylic acid resin and N,N-dimethylformamide, add 99wt% concentrated hydrochloric acid (12 times the mass of functionalized polyacrylic acid resin) to the solution at a dropping speed of 1mL / min, heat to 40°C and react for 2h, and after the reaction is completed, vacuum evaporation and vacuum drying are performed to obtain modified polyacrylic acid resin; (4) Pretreated silica ash, tetravinyltetramethylcyclotetrasiloxane, vinylboronic acid pinacol ester, azobisisobutyronitrile, and N,N-dimethylformamide were mixed in a mass ratio of 1:(0.3-0.4):(0.1-0.2):(50-60), ultrasonically mixed, heated to 70-80°C for reaction for 2-3h, and after the reaction was completed, filtered and washed with pure water for 3-4 times to obtain modified silica ash; (5) Mix the modified polyacrylic acid resin and modified silica fume in a mass ratio of 1:(0.05-0.1) to obtain a concrete composite viscosity enhancer.

3. The method for preparing a composite concrete viscosity enhancer according to claim 2, characterized in that: The eluent of the flash chromatography in step (2) is ethyl acetate / chloroform, and the elution gradient of the eluent is ethyl acetate:chloroform volume ratio from 8:2 to 1:

9.

4. The method for preparing a composite concrete viscosity enhancer according to claim 2, characterized in that: The first activation in step (2) is microwave activation with a microwave power of 100 W, a temperature of 30° C., and a time of 30 min; the second activation is microwave activation with a microwave power of 100 W, a temperature of 30° C., and a time of 1 min.

5. The method for preparing a composite concrete viscosity enhancer according to claim 2, characterized in that: The preparation method of the pretreated silica ash in step (4) is as follows: vinyltrimethoxysilane, anhydrous ethanol and pure water are mixed in a mass ratio of 1:1:5 for 10 minutes, 0.5 times the mass of vinyltrimethoxysilane is added to the silica ash, the temperature is raised to 110°C, reflux reaction is carried out for 3-4 hours, filtering and washing with anhydrous ethanol for 4 times, and vacuum drying to obtain the pretreated silica ash.

6. The method for preparing a composite concrete viscosity enhancer according to claim 5, characterized in that: The specific surface area of ​​the silica ash is 25m 2 / g.

Citation Information

Patent Citations

  • Special modified concrete admixture for high-speed rail and preparation method thereof

    CN111747673A

  • Hyperbranched concrete tackifier as well as preparation method and application thereof

    CN113637123A

  • Environment-friendly glue reducing agent for concrete and preparation method of environment-friendly glue reducing agent

    CN117865550A

  • Flourinated silane-modified polyacrylic resin

    US20140303312A1

  • Use of copolymers as tackifiers for adhesives

    WO2013167537A1

Cited By

  • Special mineral tackifier for sprayed concrete and preparation method thereof

    CN120137103A

  • A mineral thickening agent for shotcrete and a preparation method thereof

    CN120137103B

  • Early-strength tackifier for high-titanium heavy slag-based sprayed concrete and preparation method of early-strength tackifier

    CN120271264A